Students - Teachers Communication Patterns in Islamic Elementary Schools: Analyzing the Hierarchical Context of Standpoint’s Theory - Eti Nurhayati; Yayah Nurhidayah (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to identify the patterns of student-teacher communication in learning as perceived by teachers from the perspective of Standpoint Theory. This descriptive research uses questionnaires distributed to teachers. The results of this research show that first, the most dominant attitude in student communication is the desire to always please the teacher; second, the most common language use in student communication is frequent complaints; third, the most dominant verbal communication style of students is always speaking politely; fourth, the most prevalent nonverbal communication style is frequent eye contact, active listening, and silence; and fifth, the most dominant personality attitude in student communication is a lack of willingness to make sacrifices. These findings indicate that student-teacher communication remains hierarchical. Teachers are perceived to have more power compared to students, maintaining the stigma of teachers as figures to be